IMPLEMENTASI PENYELENGGARAAN PERPUSTAKAAN DI KABUPATEN KENDAL - Pradipta, Wisnu; Rostyaningsih, Dewi; Rengga, Aloysius (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
In the framework of the intellectual life of the nation, as mandated in the preamble of the Indonesia Constitution on 1945 in the fourth paragraph. The Government of the Province of Central Java has published Regulations about a Arrangement the Library, that is an activity planning, management, preservation, development, coaching and supervision of the Library. The policy was formulated to solved existing problems one of them a low interest of reading society. The purpose of the research was to find out how the Implementation of the Arrangement the Library in the District of Kendal and to know of factors support and obstacle of implementation. The method used in this research was qualitative-descriptive. Based on the results of research in the Office of Library and Regional Archives in The District Of Kendal as the main executor of Kendal government in the sector of library. That the Implementation policy of Arrangement the Library in the District of Kendal on 2014 have not been implemented maximally. Because there are still some targets achievement RPJMD library sector at Kendal in 2010-2015 has not been reached. Target performance indicators on the RPJMD yet achieved one of them is the level of library visitors. In the implementation of this policy there are still obstacles such as communications that has not been going well, limited human resources, facilities and infrastructures supporting the Library is still limited. The result of this research can be concluded that the implementation of arrangement the library in the Districtof Kendal in 2014 has not been implemented maximally. Suggestion from researcher is the Office of Library and the archive area of Kendal as implementers are expected to further improves communication in socialization of the Library and the interests of reading to the general public. Then the addition of budget to the section of Library for the procurement of non-permanent employees (npe) to fill a shortage of librarians and Library technical personnel, as well as improving infrastructure facilities of the Library.